Rapid assessment method for population estimation of softshell turtle (Amyda cartilaginea Boddaert, 1770) and reticulated python (Python reticulatus Schneider, 1801) - MARIANA TAKANDJANDJI; HENDRA GUNAWAN; VIVIN SILVALIANDRA SIHOMBING (Biodiversitas Journal of Biological Diversity, 2018)
Takandjandji M, Gunawan H, Sihombing VS. 2018. Rapid assessment method for population estimation of softshell turtle (Amyda cartilaginea Boddaert, 1770) and reticulated python (Python reticulatus Schneider, 1801). Biodiversitas 19: 265-271. The decreasing number of soft-shell turtle and reticulated python in the wild is due to high demand of the animal in local as well as international market. The condition made the Indonesian government set particular collecting and trading quota for the reptiles, but unfortunately, it does not automatically guarantee their preservation. Current collecting practices will lead to population decline and even extinction of the species since the reptiles’ population in the wild has not yet been accurately determined. The purpose of the research was to determine a rapid method of population estimation to establish a baseline for determining collecting quota for the reptiles, especially of softshell turtles and reticulated pythons. The study was conducted in East Kalimantan using the method of deep interviews of 20 respondents (exporters, fishers, traders, collectors) and 15 key respondents (government officials). The results of this survey showed that the collect reptiles were collected from the wild, since up to now, there has been no successful breeding program of reptiles. The collected reptiles were dominated by female adult softshell turtles collected from Kotabangun area which has collecting quota of 1,080/year (1/3 of the exporting quota for East Kalimantan). Softshell turtles collected from Kotabangun have bigger in stature than those found in West Java and Jakarta, and the reticulated pythons collected from Kotabangun are longer than those found in West Java and Jakarta. The number of reticulated pythons collected from Kotabangun reaches 4,800 individuals/year (1/4 of the quota set for East Kalimantan export).